Exports, Services and Value Added - A National, International and Regional Analysis for Austria - N. Bayerl; Oliver Fritz; Robert Hierlaender; G. Streicher (FIW - Research Centre International Economics, 2008)
Austrian business cycles are strongly dependent on the development of foreign exports. The paper deals with two important issues in this context: What is the impact of foreign exports on total growth in the Austrian economy? A more and more globalized economy implies that the share of foreign imports in the production of export commodities increases. This suggests that the contribution of foreign exports to domestic growth will diminish over time ? this hypothesis will be tested in the paper. In addition, the results for Austria will be compared with those for other countries in the EU as well as the OECD. Export activities are not evenly distributed over space: While some regions are more specialized in the production of commodities for the domestic market, other regions are much more dependent on foreign exports. In the paper, the regional economic consequences of the value-added impacts of foreign exports will be analysed. The paper will make use of national input-output tables for the years 1995, 2000 and 2003 as well as input-output tables for OECD countries to examine the national economic impacts of foreign exports and an international comparison. Furthermore, a multiregional model for Austria ("MultiREG") will be applied for estimating the corresponding regional impacts.
Keywords: 330; Competitiveness; Export of Services